FUNCTIONAL MODEL OF ORGANIZATION DEVELOPMENT BASED ON QUALITY MANAGEMENT IN AN EDUCATIONAL ORGANIZATIONAS A QUALITY ASSURANCE TOOL - Kenzhin, Zh.; Kuangaliyeva, T.; Kassenov, Kh. (Scientific Journal of Astana IT University, 2022)
In the context of the formation of an innovative economy, great attention in management in recent years has been paid to the problems of mastering and implementing the management of an organization based on quality. Quality management is one of the key functions of both corporate and project management, the main means of achieving and maintaining the competitiveness of any organization. The historical experience of the USA, Japan, Germany, and a number of other countries shows that ensuring the steady and harmonious development of any enterprise through the use of effective management systems based on quality is one of the main levers with which they managed to overcome the economic crisis and take a strong position in the world market. The research topic is relevant due to the great importance and significance of the integration mechanisms for the development of enterprises and organizations based on quality management. Thus, the construction of a functional model allows you to develop new solutions for bringing enterprises to a new level of development. In recent years, the role of quality in ensuring the competitiveness of products and enterprises has significantly increased, which requires the management of organizations to develop and implement modern management models that meet the requirements of international and national standards. This article discusses an algorithm for the formation and implementation of a functional model for the development of an organization based on quality management in an educational organization. The feature of quality management policy in an educational organization is analyzed. A process of forming a functional model based on standardization, which is based on the implementation of interrelated processes that increase the efficiency of an organization in obtaining the intended goals, is proposed. This article describes the algorithm of formation and realization of the functional model of development of the organization on the basis of quality management in education. Analyzed features of the policy of quality management in educational organizations. The proposed formation process of the functional model on the basis of standardization is based on the implementation of interrelated processes that increase the organization’s effectiveness in obtaining goals.